How much could refuges help us recover from a global catastrophe?. (September 2015) - Beckstead, Nick
Highlights: Global catastrophes like nuclear wars or pandemics might destroy civilization. Some propose building "refuges" to aid survival and recovery in such cases. Government/private shelters, subs, and isolated peoples serve similar goals. Refuges could only be crucial in a small portion of proposed catastrophe scenarios. Abstract: Some global catastrophes (such as nuclear wars, pandemics, or an asteroid collision) might destroy civilization. Some propose building well-stocked shelters constantly staffed with people trained to rebuild civilization in such cases. These "refuges" would have an unimpressive expected cost per life saved, but could conceivably have an impressive expected cost per future generation allowed to exist. From some ethical perspectives that highly value future generations, building refuges may therefore seem like a promising idea. However, several factors significantly dilute the potential impact of refuges, even if the proposed catastrophes occur. Government/private disaster shelters, people working on submarines, and isolated peoples who prefer to be left alone serve these purposes to some extent already. Many proposed catastrophes do too much/too little damage for refuges to help, affect the environment in ways that make refuges largely irrelevant, or otherwise give relatively limited advantages to the people in refuges. In global food crises or social collapse scenarios, refuges would add little to aggregate stocks of population, resources, food, and relevant skills; but they may add something unique in terms of isolation and coordination. These potential benefits of refuges seem the most promising, and may be worthy of further analysis.